EFFECTS OF SOCIAL NETWORKS MANAGING ON WORKING CAREER - Gilda, Antonelli; Raffaele, Corrado (European Scientific Journal, ESJ, 2014)
This work is about the co-evolution of intra-organizational networks and organizational structures and behaviors, in the context of the introduction of an innovation. A number of network studies, especially those concerned with the role of social capital in organizational settings, has focused on those actors who are most important in shaping the structural features of the network. We focus on one such actors, the broker, that is the one whose ties connect otherwise disconnected sets of network nodes. Our aim is assessing the mechanisms through which the broker legitimizes himself in his own role. In fact, existing studies mainly document the consequences of the broker network position, but do not analyze the mechanisms through which this position is acquired vis a vis the other actors in the network. In this work we address both the organizational and the individual levels of analysis. At the organizational level we analyze the evolution of intra-organizational networks in the context of an important organizational change. At the individual level we analyze how personal attributes and behaviors co-evolve with the networks, as a consequence of the actors learning processes. We will focus on one specific network member who is shown to improve his own understanding of how to perform the informal role of the broker. We will see that such informal role will be turned into a formal organizational position by the end of the period observed in this study.